2020
DOI: 10.1109/access.2020.2988493
|View full text |Cite
|
Sign up to set email alerts
|

Few-Shot Learning for Chinese Legal Controversial Issues Classification

Abstract: Chinese courts organize debates surrounding controversial issues along with the gradual formation of the new procedural system. With the progress of China's judicial reform, more than 80 million judgement documents have been made public online. Similar controversial issues identified in and among the massive public judgment documents are of significant value for judges in their trial work. Hence, homogeneous controversial issues classification becomes the basis for similar cases retrieval. However, controversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Examples of document type target variables are case type, complaint type, accusation type, and topic type, etc. [57,62,72,77,78].…”
Section: Law Articlementioning
confidence: 99%
“…Examples of document type target variables are case type, complaint type, accusation type, and topic type, etc. [57,62,72,77,78].…”
Section: Law Articlementioning
confidence: 99%
“…= ( − ) −1 (5) Where a∈R is a controlling variable, and I is the identity matrix. Next, we compute embeddings by (6). =…”
Section: B Embedding Propagationmentioning
confidence: 99%
“…Beyond foundational research, significant practical strides in few-shot learning and synthetic data have yet to be applied (and exist neither within the U.S. or Chinese government to the best of the authors' knowledge), despite a demonstrated interest. 53 There is still time before both sides start making effective use of them. If proven practical and applicable for military needs, these approaches would enable development of AI without reliance on massive datasets and might mean, in effect, that data is not the new oil; rather, it is no more than yesterday's whale oil.…”
Section: Few-shot Learningmentioning
confidence: 99%